2018
DOI: 10.1080/09513590.2017.1397116
|View full text |Cite
|
Sign up to set email alerts
|

Operation, hormone therapy and recovery of the patients with severe forms of adenomyosis

Abstract: Endometriosis is among the prevalent gynecological diseases and diagnosed in 10% of women of reproductive age. Endometriosis/adenomyosis is becoming increasingly a health-social problem, which is associated with severe clinical manifestations and recurrent disease which has a negative effect on quality of life, women ability to work and her reproductive function. This article presents modern approaches of drug therapy to treat severe forms of adenomyosis. We have reviewed recent major studies in the field of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Their mechanism of action involves inhibiting ovulation, inducing decidualization, and causing atrophy. Common side effects include bleeding, breast pain, and headaches [ 4 , 10 , 33 , 35 , 36 , 37 ]. Estroprogestins are not recommended for treating endometrial cancers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their mechanism of action involves inhibiting ovulation, inducing decidualization, and causing atrophy. Common side effects include bleeding, breast pain, and headaches [ 4 , 10 , 33 , 35 , 36 , 37 ]. Estroprogestins are not recommended for treating endometrial cancers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Common side effects include breast tenderness, weight gain, fluid retention, bleeding, acne, headaches, mood swings, and elevated liver enzyme levels. Progestins commonly used for treating endometriosis and adenomyosis include etonogestrel-releasing implants, levonorgestrel-releasing IUDs, and Dienogest [ 4 , 8 , 10 , 11 , 33 , 35 , 36 , 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have found that different patients have different responses to drug therapy in clinical practice. Previous studies have found that only half of patients can benefit from progesterone therapy 15–19 . Adenomyosis may lead to a high proportion of infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that only half of patients can benefit from progesterone therapy. [15][16][17][18][19] Adenomyosis may lead to a high proportion of infertility. With the opening of China's family planning policy, the increasing female population has fertility requirements.…”
Section: Introductionmentioning
confidence: 99%